DETERMINAN KUALITAS AUDIT BERDASARKAN STANDAR PERIKATAN DAN UKURAN KAP - Ika Nur Astuti; Yayu Putri Senjani; Slamet Haryono (Media Riset Akuntansi, Auditing & Informasi, 2022)
Financial statements are an important instrument for every company which is not only a means of making decisions by the company's internals alone, but also to assess the condition or condition of the company by external parties as well. In recent years, manipulation of audited financial statements caused by auditor violations often occurs, so that public doubts arise over the quality of audits produced by auditors. This study aims to determine the effect of audit fees, audit tenure, audit rotation and KAP size on audit quality. Sampling was carried out using the purposive sampling method and resulted in a selected sample of 59 manufacturing companies multiplied by a five-year observation period, so that the total number of observation data was 295. The research data used in this study were secondary data taken from the annual report. manufacturing company registered on ISSI from 2016-2020. This study implies a descriptive research design using a quantitative approach. Data analysis in this study uses logistic regression analysis which is processed using STATA version 16 test tool. The results of this study indicate that audit fees have a positive effect on audit quality, audit tenure and KAP size have no effect on audit quality, while audit rotation has a negative effect on audit quality.